Almost eight decades later: description of the male of Isoctenus guadalupei (Mello-Leitão, 1941) comb. nov. and redescription of the female - Polotow, Daniele; Brescovit, Antonio D. (Zootaxa, 2019)
Isoctenus Bertkau 1880 is a genus composed by medium to large sized (7 to 19 mm of total body length) Neotropical spiders (Polotow & Brescovit 2009). They are nocturnal wandering hunters, which prey in the ground and above leaf litter, as the other tropical wolf spiders of Ctenidae (Griswold et al. 2005). The genus was revised by Polotow & Brescovit (2009) and currently contains 15 species, distributed in the Parana (Atlantic, Parana, and Araucaria Forests provinces) and Chacoan (Cerrado and Pampean provinces) dominions (Morrone 2014). Polotow & Brescovit (2009) also presented a phylogenetic analysis based on morphological characters, supporting the transference of four species from Ctenus Walckenaer, 1805 to Isoctenus. Later, the genus was included by Polotow & Brescovit (2014) in a phylogenetic analysis of Cteninae, and it appears to be related to the Neotropical Parabatinga Polotow & Brescovit, 2009 and the Afrotropical Petaloctenus Jocqué & Steyn, 1997 and Africactenus Hyatt, 1954, in addition to a couple of misplaced Ctenus species.